Steps in Home Living - Ament, Karen; Reiff, Florence M. (Peoria, Illinois : Bennett & Publishing Company, 1984)
A home economics textbook discussing such topics as food preparation, nutrition, taking care of the home, consumer education, child care, personal care and grooming, and other topics.
Includes index.
Keywords: Home economics -- Juvenile literature; Beauty, Personal -- Juvenile literature; Home economics